The strategies of nutrient removal compounds from wastewater by using aquatic plants in the Green deal implementation - Larysa Sablii; Veronika Zhukova; Jakub Drewnowski (Desalination and Water Treatment)
The aim of the study was to determine the efficiency of wastewater treatment from nitrogen compounds - ammonium, nitrite, nitrate, and phosphate - using Lemna minor and Spirogyra sp. in the context of the strategies toward Green Deal Implementation. Meanwhile, the various biological treatment methods of nutrients according to the value-added and application prospects were also discussed as a future solution in the Circular Economy Model. The complementary effect of Lemna minor and other higher aquatic plants, in particular Spirogyra sp. was established. The efficiency of nitrate removal for 7 days was 86.4 %, and phosphate removal was 78 %. The concentration of NO3 - ions after treatment was 6.8 mg/dm3, and phosphate (P2O5) 2.2 mg/dm3. It was noted that the simultaneous use of an increased dose of duckweed Lemna minor and the algae Spirogyra sp. significantly increases the efficiency of nitrate removal from the experimental samples, and the efficiency of phosphate removal did not change compared to the experiment without the use of the algae Spirogyra sp. and with the use of a double dose of duckweed. Under these conditions, the nitrate removal efficiency for a duration of 7 days was 92 % and the phosphate removal efficiency was 80 %. The concentration of NO3 - ions after treatment was 4 mg/dm3, and phosphate (P2O5) 2 mg/dm3.